Anthropometrical predictors of performance in elite age group swimmers - Mitchell, L. J.; Rattray, B.; Saunders, P. U.; Pyne, D. B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A swimmer`s anthropometry is an important factor for performance. For junior swimmers many anthropometric measures have been related to freestyle and butterfly performance, with different combinations of these metrics differentiating successful males and females from their competitors [1, 2]. However these factors have not been investigated across all strokes for competition performances. Methods: Junior national-level swimmers (n=21 female, 15.4±1.2 y, 16 male, 16.7±1.1 y) were measured for height, body mass, sitting height, sum of 7 skinfolds, foot length, biliocristal breadth, anterior-posterior chest depth, and femur breadth using standardised methods [3]. Competition performances in all strokes within 3 months prior to measurements were compiled and expressed as the swimmer`s time divided by the world record for that event. Swimmers` stroke and distance preferences were determined by the event for which they were closest to the world record. The sprint and distance subgroups had best events of 200 m or less and 400 m or more respectively. Alpha level = 0.05. Results: Predictors of performance in 100 m events for males were femur breadth (r = -0.50, -0.80 to 0.00; r value, 95 % confidence limits), biacromial breadth (r = -0.58 , -0.84 to -0.12) and weight (r = -0.55, -0.82 to -0.08). Male sprinters had larger anterior-posterior chest depths (19.4 ± 0.9 cm; mean ± SD, 17.7 ± 1.1 cm) and were heavier (76.6 ± 7.4 kg, 69.1 ± 3.9 kg) than the distance specialists. For female swimmers height (r = -0.46, -0.74 to -0.03) and sitting height (r = -0.50, -0.76 to -0.08) were predictors of 100 m performance. Female sprinters were taller (172.9 ± 5.4 cm, 167.4 ± 3.5 cm), had a larger arm span (176.4 ±5.8 cm, 171.4 ± 0.5 cm) and larger feet (25.2 ± 0.9 cm, 23.9 ± 0.9 cm) than distance specialists. Discussion: Males appear to be differentiated by measures related to mesomorphy for 100 m performance. This is intuitive as muscle mass is important for short duration high-intensity performance. For females the predictors of sprint performance was related to overall stature rather than muscularity, indicating they rely less on explosive strength as a differentiating factor for 100 m performance.